PELATIHAN PERHITUNGAN PAJAK PENGHASILAN TERUTANG BAGI WAJIB PAJAK UMKM DENGAN PENGHASILAN BRUTO TERTENTU MENURUT PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 - Supadmi, N.L.; Suputra, I.D.G.D.; Budiartha, K.; Widhiyani, N.L.S. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
Community service activities aims to provide training to the taxpayer MSMEs, to be able to calculate the tax payable correctly according to government regulation number 46 year 2013. The target of this service is to provide training in 10 Taxpayers (MSMEs) in the city of Denpasar. Outcomes after this devotion completed Taxpayer (MSMEs) can measure, calculate, deposit and report their own tax obligations properly. The method of implementation service activities is carried out to provide training how to calculate the tax payable on the spot-face with the business activities of their respective owners SMEs. Results Community service activities of four (4) taxpayer SMEs using the services of a tax consultant to carry out tax obligations, four (4) did not do his tax liability on the grounds they do not know and no strikes to pay taxes, and two (2) MSMEs do their own tax liability , but did not follow the government regulation number 46 in 2013 reason does not know the new rules.